2023
DOI: 10.1158/2159-8290.22532485.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Supplementary Figure Legends from The Pancreatic Cancer Microbiome Promotes Oncogenesis by Induction of Innate and Adaptive Immune Suppression

Abstract: <p>Figure Legends for Figures S1-S8.</p>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…[10,11] For example, the mouse pancreatic cancer with abundant tumor-colonizing bacteria such as Actinobacteria, Deferribacteres, and Bifidobacterium exhibited obviously reduced responsive rate to antibodies against programmed cell death protein 1 (anti-PD-1). [12] Among various tumor-colonizing bacteria, Fusobacterium nucleatum is one of the gram-negative anaerobic bacteria and has been reported to accumulate in colorectal tumors and adenomas around colon tissues. [5,10,13,14] Recently, some studies have demonstrated that the enrichment of F. nucleatum in colorectal cancer could drive the formation of immunosuppressive tumor microenvironment (TME), [2] such as increasing the infiltration of immune suppressive cells, [15] decreasing the infiltration of tumor-infiltrating lymphocytes, [2,10] and inhibiting the killing efficiency of NK cells and T cells [16] through direct or indirect interference with metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] For example, the mouse pancreatic cancer with abundant tumor-colonizing bacteria such as Actinobacteria, Deferribacteres, and Bifidobacterium exhibited obviously reduced responsive rate to antibodies against programmed cell death protein 1 (anti-PD-1). [12] Among various tumor-colonizing bacteria, Fusobacterium nucleatum is one of the gram-negative anaerobic bacteria and has been reported to accumulate in colorectal tumors and adenomas around colon tissues. [5,10,13,14] Recently, some studies have demonstrated that the enrichment of F. nucleatum in colorectal cancer could drive the formation of immunosuppressive tumor microenvironment (TME), [2] such as increasing the infiltration of immune suppressive cells, [15] decreasing the infiltration of tumor-infiltrating lymphocytes, [2,10] and inhibiting the killing efficiency of NK cells and T cells [16] through direct or indirect interference with metabolic pathways.…”
Section: Introductionmentioning
confidence: 99%